Perceptions of adolescents regarding consequences of licit drug use to oral and general health - Gomes, Monalisa da Nóbrega Cesarino (2014)
Objective: To determine the prevalence of tobacco smoking and alcohol use and perceptions regarding the harmful effects of these drugs on both oral health and general health, comparing adolescents who have experimented with such drugs to those who have not. Methods: A cross-sectional study was carried out involving 574 adolescents at public schools in the city of Campina Grande, state of Paraíba, Brazil. Results: The prevalence of smoking was 3.3% and 54.5% of the adolescents had experimented with alcohol. A total of 88% of smokers and non-smokers believed that smoking can have a negative effect on oral health (P=0.526), with dental caries the most cited condition (38.2%; P=0.013). The vast majority (93.6%) believed that smoking can cause health problems, with no significant difference found between smokers and non-smokers (P=0.434). Cancer was the most cited consequence (44.2%; P=0.434). Among the adolescents who made use of alcohol and those who did not, bad breath was the most cited oral health consequence of alcohol use (38.3%; P=0.267) and cirrhosis was the most cited consequence to general health (23.8%); alcohol users cited cirrhosis significantly more than non-users (P=0.001). Conclusion: The prevalence of tobacco smoking was low, whereas the prevalence of alcohol use was high in the present sample. The adolescents interviewed generally demonstrated a lack of knowledge regarding the consequences of these drugs to general and oral health.